Institutional modalities for decarbonizing irrigation in Bangladesh - Mitra, Archisman; Yashodha, Yashodha; Hossain, Mofazzal; Siddiqui, Md. Belal; Mukherji, Aditi (International Water Management Institute, 2022)
Diesel-based groundwater irrigation has been crucial in expanding dry season boro paddy cultivation in Bangladesh. Boro paddy was, in turn, instrumental in ensuring the country’s food security. But high dependence on imported diesel is a financial burden for the government. Transitioning to clean and renewable energy sources, like solar, can alleviate the government’s fiscal burden and help decarbonize the agricultural sector. Bangladesh has promoted multiple models for the diffusion of solar irrigation pumps (SIPs), ranging from the conventional subsidy-driven models of SIP ownership to the fee-for-service model that leverages private sector investments for expanding the outreach of irrigation services. The fee-for-service model promoted in Bangladesh by the Infrastructure Development Company Limited (IDCOL) is unique in the South-Asian context for bringing public-private partnership in SIP expansion. This model also offers useful lessons for the provision of affordable irrigation to smallholder farmers in the region.